Komplikasi Spinal Anastesi Pada Pasien Operasi: Literature Review - Sujadi, Didi; Suharmanto, Suharmanto; Indrawan, Khadafi (CV. Jasa Sukses Abadi, 2025)
Abstract Spinal anesthesia is a commonly used anesthetic technique in various surgical procedures. Most operations are performed using spinal anesthesia rather than general anesthesia or local anesthesia. Spinal anesthesia is a regional anesthetic technique that involves injecting a local anesthetic into the subarachnoid space. Spinal anesthesia can avoid the risks of failed endotracheal intubation and the possibility of aspiration of gastric contents during general anesthesia, and can provide patient satisfaction. This article was written using a literature review method conducted through a literature search of various national and international journals. Journal articles from 2015 to 2025 served as the basis for the article used. References used were searched through the Pubmed, NCBI, and Google Scholar databases. The reading sources used were then analyzed using a systematic literature review method, which includes the activities of collecting, evaluating, and developing research with a specific focus. Spinal anesthesia, while having advantages, can also cause several complications. Complications of spinal anesthesia can include hypothermia, shivering, post-operative nausea and vomiting (PONV), post-dural puncture headache (PDPH), high or total spinal block, and urinary retention.